2021
DOI: 10.1161/circoutcomes.120.007492
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion With Rates of Utilization of Cardiovascular Therapies Among Medicaid Beneficiaries Between 2011 and 2018

Abstract: Background : The Affordable Care Act expanded Medicaid eligibility allowing low-income individuals greater access to healthcare. However, the uptake of state Medicaid expansion has been variable. It remains unclear how the Medicaid expansion was associated with the temporal trends in use of evidence-based cardiovascular drugs. Methods : We used the publicly available Medicaid Drug Utilization and Current Population Survey to extract filled prescription … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…[42][43][44][45] While there has been limited evidence to date about the association of Medicaid expansion with blood pressure control or glucose control, other work has found that expansion was associated with an improvement in quality of care process measures that may be associated with hypertension and diabetes control, such as improved glucose monitoring rates, identification of diabetes and hypertension cases, and other diabetes management measures 41,[46][47][48][49][50][51][52][53] in addition to improved access to diabetes, hypertension, and cardiovascular-related medications. [53][54][55] The Oregon Health Insurance Experiment, a randomized clinical trial that examined Medicaid insurance, failed to detect improvements in blood pressure or glucose control (likely because of insufficient statistical power) but found increases in diabetes diagnoses and the use of diabetic medications; this study followed patients for 25 months and was limited to 1 state. 56 A recent study on 178 FQHCs found that in the 2 years following ACA-related expansions, newly insured patients with diabetes at FQHCs experienced reductions in glucose and blood pressure levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45] While there has been limited evidence to date about the association of Medicaid expansion with blood pressure control or glucose control, other work has found that expansion was associated with an improvement in quality of care process measures that may be associated with hypertension and diabetes control, such as improved glucose monitoring rates, identification of diabetes and hypertension cases, and other diabetes management measures 41,[46][47][48][49][50][51][52][53] in addition to improved access to diabetes, hypertension, and cardiovascular-related medications. [53][54][55] The Oregon Health Insurance Experiment, a randomized clinical trial that examined Medicaid insurance, failed to detect improvements in blood pressure or glucose control (likely because of insufficient statistical power) but found increases in diabetes diagnoses and the use of diabetic medications; this study followed patients for 25 months and was limited to 1 state. 56 A recent study on 178 FQHCs found that in the 2 years following ACA-related expansions, newly insured patients with diabetes at FQHCs experienced reductions in glucose and blood pressure levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies that examined the 3 years following expansion have demonstrated lower mortality among patients with end-stage kidney disease and cancer as well as lower infant mortality and cardiovascular mortality in middle-aged adults . While there has been limited evidence to date about the association of Medicaid expansion with blood pressure control or glucose control, other work has found that expansion was associated with an improvement in quality of care process measures that may be associated with hypertension and diabetes control, such as improved glucose monitoring rates, identification of diabetes and hypertension cases, and other diabetes management measures in addition to improved access to diabetes, hypertension, and cardiovascular-related medications . The Oregon Health Insurance Experiment, a randomized clinical trial that examined Medicaid insurance, failed to detect improvements in blood pressure or glucose control (likely because of insufficient statistical power) but found increases in diabetes diagnoses and the use of diabetic medications; this study followed patients for 25 months and was limited to 1 state .…”
Section: Discussionmentioning
confidence: 99%
“…Despite more than a decade of policy advances through the Affordable Care Act, including in improving affordability and availability of lower-cost drugs, an estimated 29 million US residents do not have insurance and lack prescription coverage, many of whom are Black individuals and Hispanic individuals. 7 Of the population with insurance, millions more individuals are enrolled in current plans that leave them without enough insurance and responsible for paying a significant portion of their prescription costs. To achieve pharmacoequity will require adoption of universal, low-cost prescription drug coverage that fills gaps for individuals with insurance and provides medication coverage to all individuals who do not have insurance.…”
Section: Enhancing Access To Therapeutic Carementioning
confidence: 99%
“…Such coverage includes expanding Medicaid in states that have not yet done so. Medicaid expansion has been shown to be associated with improved rates of prescribing of evidence-based cardiovascular pharmacotherapies, medications for opioid use disorder, and oral contraceptives, among other drugs . Health inequities have also been reduced or eliminated in care settings that offer uniform drug coverage, suggesting that such an approach may reduce overall health care costs and equitably improve quality of life.…”
Section: Enhancing Access To Therapeutic Carementioning
confidence: 99%
“…The association between visits to a health professional in the past year and rates of BP control have been reported in prior studies [7,32]. The Affordable Care Act expanded healthcare coverage to millions of adults in the US and resulted in an increase in antihypertensive medication use in states that expanded Medicaid [33,34]. Additional state and federal health insurance expansions should be considered in the future in order to increase persistent BP control and prevent CVD.…”
Section: Plos Onementioning
confidence: 77%